Sieving potato clones for genetic resistance to the potato white worm Premnotrypes vorax (Hustache) - VALENCIA-V., LUIS; BOHÓRQUEZ, CARLOS (Revista Colombiana de Entomología, 1994)
To screen nine commercial cultivars and 13 clones of potato of the Colombian Central Collection (CCC), the plastic container test was used. Potato tubers of approximately 60 g were buried into a layer of vegetal soil inside the plastic containers. The tubers were artificially infested with a known number of first instar larvae of the Andean weevil. The food preference of the adults was also investigated among the clones of the CCC. AH the experiments were carried out under screen house conditions, at ICA 's National Center of Research «Tibaitatá» in Mosquera (Cund.). All the screened materials were very susceptible to the attack of the insect on the tubers. The results are discussed based on recently published research.